PENGARUH MANAJEMEN MODAL KERJA PADA PROFITABILITAS LEMBAGA PERKREDITAN DESA - Rai Suryawan, I Gusti Ngurah; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2016)
Factors affecting working capital management is closely related to the level of cash turnover, accounts receivable turnover rate, debt to total assets and debt to equity ratio. The purpose of this study was to determine the effect of cash turnover, accounts receivable turnover rate, debt to total assets and debt to equity ratio to Profitabilitas Population  in this study were all LPD in sub mengwi. The samples used were 38 samples with nonprobability sampling method. Methods of data collection using the documentation techniques. The analysis technique used is multiple linear regression analysis. Based on the analysis and hypothesis testing can be concluded that the variable rate cash turnover, accounts receivable turnover rate, debt to total assets and debt to equity ratio positive effect on profitability.
Keywords: Profitability, Turnover Rate Cash, Accounts Receivable Turnover Rate, Debt To Total Assets, Debt To Equity Ratio